Indonesian Subtitling and Dubbing of The Protagonist’ Declarative Utterances in_Superbook_Series, Episode “Jonah”: A Study of Strategies and Error Analysis - Nova Natalia Heryadi; Harris Hermansyah Setiajid (Universitas Muhammadiyah Semarang, 2023)
Subtitling and dubbing are crucial translation services that enable viewers to enjoy content from different countries without language barriers. The quality of these translations significantly impacts the viewing experience. This study aims to (1) analyze the translation strategies employed by machine translators (MT) and human translators (HT) in subtitling and dubbing, and (2) identify and categorize translation errors concept of declarative utterances by the protagonist in the Superbook series titled Jonah. The research employs Gottlieb's theory of subtitling strategies and Koponen's theory of error translation. The data collection and analysis involve library research to gather expert information and explicatory research for an in-depth examination of the translations. This approach allows for a comprehensive understanding of the translation processes and potential improvements in the subtitling and dubbing industries. The results reveal 23 errors in both machine and human translations. Dubbing errors predominantly involve substituted concepts (8), indicating contextually appropriate or valid word replacements chosen by human translators. In contrast, subtitling errors frequently involve mistranslated concepts (3), suggesting inaccuracies in machine translations. Human translators in dubbing often use paraphrase (5) strategies to enhance translation efficiency and address unreconstructed patterns in the source text. Machine translators in subtitling predominantly employ the transfer strategy (10), retaining the source language words in the target language without alteration. This study highlights the importance of understanding translation strategies and errors in subtitling and dubbing to improve translation quality and enhance the viewing experience for audiences worldwide.